2022
DOI: 10.3390/met12111952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersion Time in Chloride Solution on the Properties of Structural Rebar Embedded in Alkali-Activated Slag Concrete

Abstract: The electrochemical impedance spectroscopy (EIS) technique is widely used in the study of the corrosion of metallic materials. This method also allows for the electrical characterization at the ceramic–metal interface in contact with an aqueous solution composed of chloride ions. EIS makes it possible to discriminate the contribution of the phenomena that occur in the interface to determine the porosity of the cementitious material. The porosity determines the degree of corrosion of the metallic material and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Aperador et al [10] investigated the corrosion resistance of structural rebar embedded in non-Portland cement alkali-activated slag concrete. The effect of immersion time in chloride solution was investigated.…”
Section: Contributionsmentioning
confidence: 99%
“…Aperador et al [10] investigated the corrosion resistance of structural rebar embedded in non-Portland cement alkali-activated slag concrete. The effect of immersion time in chloride solution was investigated.…”
Section: Contributionsmentioning
confidence: 99%
“…The authors in Refs. [28][29][30][31] analyzed the influence of chloride ions and described the electroosmotic effect as a process of movement intensification in capillary-porous objects. The analyses showed that this process can descriptively characterize the electrochemical reaction of oxygen reduction in concrete, as well as the electrolysis of water.…”
Section: Introductionmentioning
confidence: 99%